2011
DOI: 10.1152/ajpheart.00508.2010
|View full text |Cite
|
Sign up to set email alerts
|

Decrease in the density of t-tubular L-type Ca2+ channel currents in failing ventricular myocytes

Abstract: In some forms of cardiac hypertrophy and failure, the gain of Ca(2+)-induced Ca(2+) release [CICR; i.e., the amount of Ca(2+) released from the sarcoplasmic reticulum normalized to Ca(2+) influx through L-type Ca(2+) channels (LTCCs)] decreases despite the normal whole cell LTCC current density, ryanodine receptor number, and sarcoplasmic reticulum Ca(2+) content. This decrease in CICR gain has been proposed to arise from a change in dyad architecture or derangement of the t-tubular (TT) structure. However, th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
57
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 37 publications
(61 citation statements)
references
References 36 publications
4
57
0
Order By: Relevance
“…While several groups have shown that LTCC currents are reduced in both experimental48 and human495051 heart failure, others reported only little differences52. In this context it is important to note that LTCC currents not only initiate excitation–contraction coupling in cardiac muscle, but have also been implicated in calcium-dependent signalling in cardiomyocytes.…”
Section: Discussionmentioning
confidence: 99%
“…While several groups have shown that LTCC currents are reduced in both experimental48 and human495051 heart failure, others reported only little differences52. In this context it is important to note that LTCC currents not only initiate excitation–contraction coupling in cardiac muscle, but have also been implicated in calcium-dependent signalling in cardiomyocytes.…”
Section: Discussionmentioning
confidence: 99%
“…The morphology of the heart was evaluated as previously described (Horiuchi-Hirose et al, 2011). Briefly, the hearts were fixed in 20% phosphate-buffered formalin at room temperature for 24 h and cut transversely to obtain ventricular cross sections.…”
Section: Gross and Histological Evaluation Of Heartsmentioning
confidence: 99%
“…Cardiac function was assessed with ultrasound cardiography (GE Yokogawa Medical System K.K., Tokyo, Japan) in anesthetized mice as previously described (Horiuchi-Hirose et al, 2011). Briefly, hearts were viewed at the level of the papillary muscles in the short axis.…”
Section: Ultrasound Cardiographymentioning
confidence: 99%
See 2 more Smart Citations